(untitled) (Revista cientifica In Vestigium Ire, 2019)
The objective of this article is to offer readers a documentary review of the lnternational Standard of Quality Control (NICC1), given the current ignorance of the companies about its form, scope and importance, in such a way that the reader manages to appropriate the content and its fundamental components such as its scope, applicabi lity, objectives, definitions that frame and limit it to abstract the requirements that must be applied by the audit firms and the independent accountants that exercise the audit activity. In the same way, to sensitize the Public Accounting professionals and in the process of formation so that they tend in the assignments far an audit with quality.